(untitled) (Revista Nacional de Odontología, 2020)
Objective: This non-randomized controlled clinical trial compared a new finishing protocol UDEA2 with the UDEA1 finishing protocol, according to the Objective Grading System (ogs). Methods: Forty-one patients treated in the postgraduate orthodontics clinic were included. Twenty patients served as intervention group (ig) with whom was used the UDEA2 protocol which includes dental positioners, and were compared to twenty-one patients that served as control group (cg) with whom was used the UDEA1 finishing protocol. An orthodontist (gold standard) determined the required movements with positioners used in the UDEA2 protocol. Eight ogs variables were measured by a calibrated clinician. Results: Both groups were comparable in gender, age and severity, but not in type of treatment applied. The total ogs for gc was 28.9±10.0, for ig at T1 (before the positioner) was 20.4±6.0 and the score for ig at T2 (after the positioner) was 19.2±6.0, with statistically significant differences (P≤0.05). The ogs score was principally increased for “alignment” in gc and ig-T1 groups. This variable decreased significantly in the ig-T2 group. There were no patients with more than 30 points in the ig-T2. The regression analysis showed an association (P=0.002) between the finishing protocol applied and the final ogs score. Possibility of belonging to the ig-T2 decreases as the ogs score increases (odds ratio [or] 0.83; 95% confidence interval [CI] 0.738, 0.933). Conclusions: The implementation of the UDEA2 finishing protocol, which includes an orthodontics student’s constant training, a Finishing Protocol Guide application, and a dental positioner in the finishing phase, showed an improvement in quality of orthodontic treatments.